Robots and the people who love them : holding on to our humanity in an age of social robots - Herold, Eve (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2024)
"The latest developments in robotics and artificial intelligence and a preview of the coming decades, based on research and interviews with the world's foremost experts. If there's one universal trait among humans, it's our social nature. Having relationships with others is a hard-wired need that literally shapes us and the lives we lead. The craving to connect is universal, compelling, and frequently irresistible. This concept is central to Robots and the People Who Love Them. This book is about socially interactive robots and how they will transform friendship, work, home life, love, warfare, education, and nearly every nook and cranny of modern life. It is an exploration of how we, the most gregarious creatures in the food chain, could be changed by social robots. On the other hand, it questions how will we remain the same, and how will human nature express itself when confronted by a new class of beings created in our own image? Drawing upon recent research in the development of social robots, including how people react to them, how in our minds the boundaries between the real and the unreal are routinely blurred when we interact with them, and how their feigned emotions evoke our real ones, science writer Eve Herold takes readers through the gamut of what it will be like to live with social robots and still hold onto our humanity. This is the perfect book for anyone interested in artificial intelligence, robotics, and what they mean for our future"--